Fat Grafting after Invasive Breast Cancer: A Matched Case-Control Study. Issue 6 (June 2017) - Petit, Jean Yves; Maisonneuve, Patrick; Rotmensz, Nicole; Bertolini, Francesco; Rietjens, Mario
Abstract : Background: Fat grafting has been widely indicated for postmastectomy and postlumpectomy breast reconstruction. The literature emphasizes the clinical efficacy of fat grafting, but experimental studies raise important questions about the recurrence risk because of the stimulation of remaining cancer cells by progenitor or adult adipocytes. Because breast conservative treatment provides a higher risk of residual cancer cells in the breast tissue compared with mastectomy, the authors set up a matched case-control study of fat grafting versus no fat grafting after breast conservative treatment. Methods: The authors collected data from 322 consecutive patients operated on for a primary invasive breast cancer who subsequently underwent fat grafting for breast reshaping from 2006 to 2013. All patients were free of recurrence before fat grafting. For each patient, the authors selected one patient with similar characteristics who did not undergo fat grafting. Results: After a mean follow-up of 4.6 years (range, 0.1 to 10.2 years) after fat grafting, or a corresponding time for controls, the authors observed no difference in the incidence of local events (fat grafting, n = 14; controls, n = 16; p = 0.49), axillary nodes metastasis (fat grafting, n = 3; controls, n = 6; p = 0.23), distant metastases (fat grafting, n = 14; controls, n = 15; p = 0.67), or contralateral breast cancer (fat grafting, n = 4; controls, n = 4; p = 0.51). Conclusion: Fat grafting seems to be a safe procedure after breast conservative treatment for breast cancer patients. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.